Особливості продихового апарату листків сортів груші у зв′язку з їх посухостійкістю - Толстолік, Людмила Миколаївна; Толстолик, Людмила Николаевна; Tolstolik, Liudmyla (СГІ–НЦНС, 2020)
EN: In the Southern Steppe zone of Ukraine, being the unstable humidification zone, the uppermost physiological property of pear varieties is their drought resistance. It is considered that this adaptive property is associated with the anatomical structure of the leaf. Researching stomata quantity and size in 22 pear varieties, differing to drought tolerance, confirmed it as general trend.
Keywords: груша; посухостійкість; продихи; сорти